Phylogenetic Reassessment of Acianthera (Orchidaceae: Pleurothallidinae) - Pupulin, Franco (2016)
The phylogenetic relationships within the Acianthera affinity are re-evaluated using Bayesian analyses of nrITS and chloroplast matK sequence data. Emphasis is made on species from the Antilles, Central America and the Andean South America as those have been less represented in previous studies. Acianthera is retrieved largely monophyletic, but is redefined to include the genera Aberrantia, Antilla, Apoda-prorepentia, Arthrosia, Brenesia, Cryptophoranthus, Didactylus, Dondodia, Kraenzlinella, Ogygia, Pleurobotryum, Proctoria, Sarracenella and Unguella. Four well-supported subgenera are proposed for Acianthera and characterized both geographically and morphologically. The species belonging to the three newly proposed subgenera are listed.